Students' Ways of Experiencing Human-Centered Design - Zoltowski, Carla B.; Oakes, William C.; Cardella, Monica E. (Journal of engineering education (Washington, D.C.), 2012)
Background Design is a central and distinguishing activity of engineering and one of the core criteria for evaluating and accrediting engineering programs. Design is also a subject area that poses many challenges for faculty, and incorporating human‐centered design approaches—approaches in which designers have as a focus the people they are designing for—poses additional challenges. Human‐centered approaches to design contribute to innovations in engineering design and have been shown to increase productivity, improve quality, reduce errors, improve acceptance of new products, and reduce development costs. In today's globally competitive economy, it is more important than ever to develop effective design skills within the undergraduate years. Purpose (Hypothesis) Before effective design learning experiences to develop the skills needed for human‐centered design can be created, an understanding of the ways in which students understand and experience human‐centered design is needed. This study addresses this need by investigating the qualitatively different ways in which students experience human‐centered design. Design/Method A phenomenographic framework was used to guide the methodology of the study while the literature and research on human‐centered design informed the construction of the study and provided ways to interpret the data and situate the findings. Thirty‐three student designers from a variety of academic contexts were interviewed using a semi‐structured, open‐ended approach in which they discussed concrete experiences “designing for others,” and reflections and meanings associated with those experiences. Results Analysis of the data yielded seven qualitatively different ways in which the students experienced humancentered design; these seven categories of description formed a two‐dimensional outcome space. Five of the categories were nested hierarchically. From less comprehensive to more comprehensive, those categories included: Human‐centered design as “User as Information Source Input to Linear Process,” “Keep Users' Needs in Mind,” “Design in Context,” “Commitment” and “Empathic Design.” Two categories represented ways of experiencing human‐centered design that were distinct: design was not humancentered, but “Technology‐Centered” and human‐centered design was not design, but “Service.” Conclusion This study found that i) students' understanding of the user and ii) their ability to integrate that into their designs are related in the development of more comprehensive ways of experiencing human‐centered design, and a conception of both aspects is needed. Furthermore, critical or immersive experiences involving real clients and users were important in allowing the students to experience human‐centered design in more comprehensive ways.